2015
DOI: 10.1016/j.nano.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity studies of coumarin 6-encapsulated polystyrene nanospheres conjugated with peanut agglutinin and poly(N-vinylacetamide) as a colonoscopic imaging agent in rats

Abstract: We are investigating an imaging agent that detects early-stage primary colorectal cancer on the mucosal surface in real time under colonoscopic observation. The imaging agent, which is named the nanobeacon, is fluorescent nanospheres conjugated with peanut agglutinin and poly(N-vinylacetamide). Its potential use as an imaging tool for colorectal cancer has been thoroughly validated in numerous studies. Here, toxicities of the nanobeacon were assessed in rats. The nanobeacon was prepared according to the synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…The particle size and zeta potential were measured in neutral solution whose pH corresponded to that of the administration site (the large intestine) of the nanobeacon. The characteristics were almost identical to those described previously [26,27,29,30,31]. Our past study on the stability of the nanobeacon indicated that the characteristics would be constant through the current research [29].…”
Section: The Reproducibility Of the Nanobeaconsupporting
confidence: 83%
See 3 more Smart Citations
“…The particle size and zeta potential were measured in neutral solution whose pH corresponded to that of the administration site (the large intestine) of the nanobeacon. The characteristics were almost identical to those described previously [26,27,29,30,31]. Our past study on the stability of the nanobeacon indicated that the characteristics would be constant through the current research [29].…”
Section: The Reproducibility Of the Nanobeaconsupporting
confidence: 83%
“…The characteristics were almost identical to those described previously [26,27,29,30,31]. Our past study on the stability of the nanobeacon indicated that the characteristics would be constant through the current research [29]. All batches were used for mouse studies.…”
Section: The Reproducibility Of the Nanobeaconsupporting
confidence: 58%
See 2 more Smart Citations
“…As expected, the BCP particles were initially spherical with PS-outermost layer because of the preferential hydrophobic interactions of PS with alkyl chains of both N-CTAB and C-CTAB (Figure 3b). 48,54,60 The BCP particles were then sequentially irradiated at 420 nm, followed by 254 nm to investigate the resulting shape and morphological changes (Figures 3b−d). Irradiation at 420 nm led to a transformation of particle shape from spheres with onion-like morphology to prolate ellipsoids with stacked lamellar morphology.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%